Kadar Kasium Serum pada Pasien Diabetes Mellitus Tipe 2 di RSUD Dr. Doris sylvanus palangkaraya - Dwi Purbayanti; Nirma Jayanti; Noor Fadillah (Borneo Journal of Medical Laboratory Technology, 2020)
Insulin and glucogone secretion, and insulin resistance are processes that depend on calcium homeostasis. This study aims to determine patients with type 2 diabetes mellitus has been increase in serum calcium levels. The subjects of this study are 34 famale patients aged ≥40 years old with type-2 diabetes mellitus were selected by purposive sampling technique. This study was conducted in June 2018. Measurement of serum calcium levels was at the University Muhammadiayah Palangkaraya using Arsenazo method with BTS 350 instruments. The results showed 79% of type-2 diabetes mellitus patients had serum calcium levels >normal (>10 mg/dL) and 21% normal calcium levels. The correlation is very weak between serum calcium levels on age, duration and GDP. Serum calcium levels are seen to increase in patients with type-2 diabetes mellitus with complications of heart disease. In this study we found the increasing serum calcium levels in type-2 diabetes mellitus patients and could be used in the treatment of diabetic patients.